Shoulder joint torque analysis in young swimmers - Wiazewicz, A. (Journal of Kinesiology and Exercise Sciences, 2016)
Purpose: The evaluation of human muscle ability to generate force seems reasonable in various pathological conditions. Swimming represents an activity in which harmonic development is achieved, in both body segments. Nevertheless, shoulder pain or injuries are the most common muscular problem experienced by sport swimming athletes.Basic procedures: The study group comprised of five male subjects, competitive swimmers. They were Polish Championship finalists (16-year-olds, II sports class, age 15.74 (0.16) years, training experience 8,.8 (1.3) years). Measurements were made on the Biodex System 4isokinetic dynamometer. Flexion and extension movements were performed: protocol 1: 3 repetitions; 60 degrees/sec; protocol 2: 20 repetitions; 180 degrees/sec. Torque diagrams of shoulder extension were analyzed.Main findings: Average peak torque, maximum repetition work, total work and coefficient of variation were higher in extension. No significant differences between sides were found, but there were high individual deficits in selected parameters. Average agonist to antagonist ratio score for the left shoulder was lower. Analyzing the torque diagrams allowed to find individual disorders. Training experience was highly positively correlated with peak torque deficit in flexion (0.88) but negatively with work fatigue in flexion (right shoulder: -0.76; left shoulder: -0.66).Conclusions: It is necessary to start a compensatory strengthening program to improve shoulder efficiency and cause the achievement of bilateral, balanced development of young swimmers` bodies. The mentioned swimmers should take special care of themselves and use preventive measures to avoid shoulder trauma. In case of injury, the results of the above tests can be used to restore the appropriate condition of a swimmer`s shoulder joint.